YESUS SEBAGAI GURU TELADAN DALAM PERSPEKTIF PANTEKOSTA KHARISMATIK: JESUS AS THE EXEMPLARY TEACHER IN THE CHARISMATIC PENTECOSTAL PERSPECTIVE - Talizaro Tafonao (Sekolah Tinggi Teologi Satyabhakti, Malang)
In this article, the author studies the Synoptic Gospel of Jesus as an exemplary teacher in the charismatic perspective of charisma. This study stems from the author's anxiety over the condition of God's servants / teachers, where educators have now lost direction in fulfilling their duties as teachers. As a result, teachers are no longer a figure or model for learners and the general public. With that in mind, the author paints Jesus as an exemplary teacher in empirical experience. According to the study done by the author in this article, there are two important things to learn, Jesus as a prayer. Jesus' devotion to prayer has inspired many people, including the ministers of the charismatic pantheon, to be specifically the teachers of the Christian religion. Next, Jesus as a teacher. Teaching is a very important task in His ministry while He is in the world. Jesus' uniqueness as an exemplary teacher has greatly influenced human behavior for generations, and even these people have been the catalysts for that change until recently. This is evident from the very dynamic and popular activity of the Pentecostal Church in continuing the church's reform activity. Therefore, this paper is a case study of charismatic phenomena by incorporating the activities of popular religious figures as the objects of recent studies which further emphasize the biographical and personalities of the figures as biologically central. === Dalam tulisan ini, penulis melakukan kajian terhadap Injil Sinoptik tentang Yesus sebagai guru teladan dalam perspektif pantekosta kharismatik. Kajian ini berangkat dari kegelisahan penulis terhadap kondisi para pelayan Tuhan/pengajar, di mana para pendidik sekarang ini telah hilang arah dalam menunaikan tugas sebagai guru. Akibatnya, guru tidak lagi menjadi figur atau teladan bagi peserta didik dan kepada masyarakat pada umumnya. Dengan persoalan itu maka penulis mengupas tentang Yesus sebagai guru teladan dalam pengalaman empiris. Berdasarkan kajian yang dilakukan oleh penulis dalam tulisan ini, maka ada dua hal penting yang perlu dipelajari, yakni Yesus sebagai pendoa. Keteladanan Yesus sebagai pendoa telah menginspirasi banyak orang termasuk para pelayan-pelayan di kalangan kaum pantekosta kharismatik secara khusus guruguru Agama Kristen. Selanjutnya, Yesus sebagai ahli pengajar. Mengajar merupakan tugas yang amat penting dalam pelayanan-Nya selama Dia ada di dunia. Keunikan Yesus sebagai guru teladan telah banyak mempengaruhi perilaku manusia dari generasi ke generasi, bahkan orang-orang tersebut telah menjadi pelaku dari perubahan itu sampai sekarang ini. Hal ini nampak dari aktivitas orang-orang Pantekosta yang sangat dinamis dan populer dalam meneruskan kegiatan reformasi gereja. Oleh karena itu, tulisan ini merupakan studi pantekosta kharismatis dengan memasukkan aktivitas tokoh agama populer sebagai objek kajian baru yang selama ini lebih menekankan popularitas dan pribadi sang tokoh secara biografis sebagai sentral.